Capacity Building in Fiscal Incidence Analysis : Lessons and Reflections from the Field - World Bank (Washington, DC: World Bank, 2022)
Fiscal Incidence Analysis (FIA) is the study of how fiscal policies benefit (or burden, in the case of taxes) people and households at different parts of the income distribution. The objective of this note is to highlight lessons learned in capacity building and skill transfer for FIA, including Commitment to Equity (CEQ) assessment. The goal is to uncover effective strategies for transferring the skills and capacities to government officials and other fiscal experts in countries around the world to enable them to carry out this type of analysis themselves. The note is based on interviews with experts, both within and outside of the World Bank who have been conducting FIA assessments and building and using microsimulation tools, often in close collaboration with officials from the government. The rest of this note: (i) describes the common engagement models and capacity building approaches that have been taken; (ii) assesses the extent to which these have been successful and distils lessons learned from some of these efforts, and (iii) identifies a few concrete ways in which similar efforts in the future could be made more effective.